PENGUATAN LINGKUNGAN HIDUP MELALUI PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA KERASIKAN MASJID KELURAHAN CURUG MANIS - Budi Mulyati; Nur Hidayanti (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Poor waste management makes the quality of the environment decline. One of the cause of poor waste management was the increasing number of people accompanied by the increasing level of population consumption. However, this is not accompanied by increasing in quality of waste management. This happened because there was no internalized good understanding of waste, that every resident who lives will produce waste every day. This had become one of the focuses of work in community service activities carried out by lecturers with group 5 students at Banten Jaya University. Several work programs carried out in order to foster an understanding of the importance of waste management include a socialization program for waste sorting and the establishment of a waste bank, as well as a program for making biopore holes. This activity was carried out in a series of service activities for one month which taken place in Curug Manis Village, precisely in RT.007 RW.002 Kerasikan Masjid.